2003
DOI: 10.1016/s0925-4439(03)00109-1
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid cleavage products modify respiratory burst and induce apoptosis of human neutrophils

Abstract: Carotenoid supplementation in the treatment of diseases associated with oxidative stress has been recently questioned because of the cell damage and the increased risk of lung cancer in male smokers. Because of the complex role of neutrophils in lung diseases, we investigated whether carotenoid derivatives could affect respiratory burst and apoptosis of human neutrophils purified from peripheral blood. Stimulation of superoxide production was induced by nanomolar and micromolar concentrations of carotenoid cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Neutrophil apoptosis may be another reason for the diminished superoxide production by neutrophils in the presence of high CBP concentrations. Indeed, 20 AM CBP stimulate intracellular caspase 3 activity and chromatin fragmentation both in neutrophils [87] and in T-lymphoblast cell line [93]. Fig.…”
Section: H H H H H H H H H H H-carotene Breakdown Products Modify Resmentioning
confidence: 81%
See 2 more Smart Citations
“…Neutrophil apoptosis may be another reason for the diminished superoxide production by neutrophils in the presence of high CBP concentrations. Indeed, 20 AM CBP stimulate intracellular caspase 3 activity and chromatin fragmentation both in neutrophils [87] and in T-lymphoblast cell line [93]. Fig.…”
Section: H H H H H H H H H H H-carotene Breakdown Products Modify Resmentioning
confidence: 81%
“…In contrast, at concentrations slightly higher than those required to enhance the cell response, CBP inhibit superoxide production by PMA-activated neutrophils [87]. On the other hand, if the chemotactic peptide f-Met-Leu-Phe is used instead of PMA to trigger neutrophil response, inhibition of superoxide production is observed even at micromolar concentrations of CBP.…”
Section: H H H H H H H H H H H-carotene Breakdown Products Modify Resmentioning
confidence: 90%
See 1 more Smart Citation
“…Probably the best example of protection conferred by carotenoids against damage generated by phagocytes originates from the study of Staphylococcus aureus, where a mutant strain with disrupted carotenoid synthesis was less able to resist a neutrophil oxidative burst (Liu et al, 2005). Adding different carotenoids to mammalian inflammatory cell cultures can remarkably inhibit oxidative burst (Murakami et al, 2000;Siems et al, 2003;Walrand et al, 2005). Further, dietary carotenoid supplementation can impair the phagocytosis ability of avian blood (McGraw and Klasing, 2006) and suppress inflammation (Koutsos et al, 2003;Koutsos et al, 2006;Meriwether et al, 2010;Shanmugasundaram and Selvaraj, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to our data here, other studies have indicated that exposure to a mixture of -carotene breakdown products induced cytotoxicity and apoptosis in normal animal cells. 14,15) Most of these breakdown products were prepared by hypochlorous acid, and the effects of the photodegradation products of carotenoid prepared by UVA irradiation are largely unknown. The breakdown products induced by hypochlorous acid could be different from the photodegradation products of carotenoids formed by UVA irradiation, so that some of the breakdown products may show cytotoxicity in normal cells.…”
Section: Discussionmentioning
confidence: 99%